ЖАМИЯТИМИЗДА ИСЛОМ ҚАДРИЯТЛАРИНИ ШАКЛЛАНТИРИШНИНГ РОЛИ - Маҳмудова, М. (SCIENCE and SOCIETY, 2020)
In the article the author studies the role of development of Islam culture, the notion of moral, aesthetic, humanistic knowledge based on Islamic rituals, in modern society saving new generation from poor morality and its place, particular issues related to religion praying, bringing up children in the spirit of Islam.
Keywords: value; family; religion; spirituality; coguition; heritage; education